Chronic exposure to sub-lethal concentration of a glyphosate-based herbicide alters hormone profiles and affects reproduction of female Jundia (Rhamdia quelen) - Soso, Auren Benck; Barcellos, Leonardo Jose Gil; Ranzani-Paiva, Maria Jose; Kreutz, Luiz Carlos; Quevedo, Rosmari Mezzalira; Anziliero, Deniz; Lima, Marina; da Silva, Leonardo Bolognesi; Ritter, Filipe; Bedin, Alexandra Calliari; Finco, Jovani Antonio (Elsevier B.V., 2007)
This work was carried out to verify the effect of a glyphosate-based herbicide on Jundia hormones (cortisol, 17 beta-estradiol and testosterone), oocyte and swim-up fry production. Earthen ponds containing Jundia females were contaminated with glyphosate (3.6 mg/L); blood samples were collected from eight females from each treatment immediately before, or at 1, 10, 20 30 and 40 days following contamination. A typical post-stress rise in cortisol levels was observed at the 20th and 40th days following exposure to glyphosate. At the 40th day, 17 beta-estradiol was decreased in the exposed females. A similar number of oocytes were stripped out from females from both groups, however, a lower number of viable swim-up fry were obtained from the herbicide exposed females, which also had a higher liver-somatic index (LSI). The results indicate that the presence of glyphosate in water was deleterious to Rhamdia quelen reproduction, altering steroid profiles and egg viability. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: glyphosate; endocrine disruption; cortisol; estradiol; testosterone; Rhamdia quelen